NEO-CONSERVATISM IN THE USA FROM LEO STRAUSS TO IRVING KRISTOL - Khuroshvili, Giorgi (European Scientific Journal, ESJ, 2012)
The article deals with the issues and problems concerning neo-conservative ideology in the USA. Until now, discussions continue to run high about adversity and joy of this political ideology. In order to clarify neo-conservative ideology and its transformation, the author of the article discusses two most important figures – Leo Strauss and Irving Kristol who are considered to be the founders of neo-conservative ideology in practical politics as well as in the discourse of political philosophy.